2002
DOI: 10.1093/jnci/94.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Neurotropic Polyomavirus JCV Late Gene Product Agnoprotein in Human Medulloblastoma

Abstract: Our data provide evidence that the JCV late gene encoding the auxiliary agnoprotein is expressed in tumor cells. The finding of agnoprotein expression in the absence of T-antigen expression suggests a potential role for agnoprotein in pathways involved in the development of JCV-associated medulloblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 28 publications
4
107
2
1
Order By: Relevance
“…19,[43][44][45] In several studies, the human neurotropic polyomavirus JC (JCV) DNA has been detected in human brain tumors including medulloblastoma. 13,40,46,47 The oncogenic potential of this virus has been established in experimental animals. Intra-cerebral inoculation of JCV into owl and squirrel monkeys results in astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,[43][44][45] In several studies, the human neurotropic polyomavirus JC (JCV) DNA has been detected in human brain tumors including medulloblastoma. 13,40,46,47 The oncogenic potential of this virus has been established in experimental animals. Intra-cerebral inoculation of JCV into owl and squirrel monkeys results in astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…Since JCV T-antigen has been detected in some medulloblastoma biopsies, 13,40 and its presence sensitizes medulloblastoma cell lines to genotoxic treatments ( Fig. 1), we asked whether JCV T-antigen affects molecular mechanisms responsible for DNA repair of DSBs.…”
Section: Dna Repair Of Double Strand Breaksmentioning
confidence: 99%
See 1 more Smart Citation
“…In two separate studies of 43 well-characterized medulloblastomas, nearly 77% were shown to contain viral DNA corresponding to the N-terminal region of JCV T-antigen, while 36% of the tumors analysed by immunohistochemistry showed regions of the tumor with nuclear positivity for T-antigen (Figure 3, Panels a, b, c). In one study, the expression of the JCV late protein, Agnoprotein, was detected in 69% of tumor samples (Del Valle et al, 2002a). Agno is an auxiliary protein whose function remains unclear; however, recently it has been shown to be expressed early in viral infection and can interact with T-antigen to regulate viral transcription and replication (Safak et al, 2001).…”
Section: Association Of Jcv With Human Brain Tumorsmentioning
confidence: 99%
“…Genomic sequences of these viruses have been reported in different human tumor types. JCV has been found in a large percentage of brain tumors, such as astrocytomas, oligoastrocytomas, glioblastomas, and ependymomas (Kunitake et al, 1995;Rencic et al, 1996;Bofill-Mas and Girones, 2001;Del Valle et al, 2002), in colorectal cancers (Bofill-Mas and Girones, 2001; Del Valle et al, 2002) and in gastric cancers (Shin et al, 2006;Murai et al, 2007). Hachana et al have found that JCV DNA in 23% of BC cases In Tunisian population, and have highlighted the inverse correlation between JCV infection and the expression of estrogen (P = 0.022) and progesterone (P = 0.008) receptors.…”
Section: Tnbc and Virusesmentioning
confidence: 99%